Morse Functions on Cobordisms - Sharko, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We study the homotopy invariants of crossed and Hilbert complexes. These invariants are applied to the calculation of exact values of Morse numbers of smooth cobordisms.